La autonomía privada y los derechos fundamentales : los intereses generales, mandato constitucional - López Pina, Antonio (Teoría y Realidad Constitucional, 2007)
In this article the author meditates on the main problem of our societies, on which Tocqueville already pointed out what can be made so that in popular government‘s equitable society governs the empire of the law and not the despotism. Our architecture constitutional part of the private autonomy but this freedom can only reconcile with the freedom of the others ones when it is limited through the public interest. The author explains it with several examples.